2017
DOI: 10.1080/09168451.2017.1313696
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the regulation of phytohormone receptors

Abstract: Phytohormones are central players in diverse plant physiological events, such as plant growth, development, and environmental stress and defense responses. The elucidation of their regulatory mechanisms through phytohormone receptors could facilitate the generation of transgenic crops with cultivation advantages and the rational design of growth control chemicals. During the last decade, accumulated structural data on phytohormone receptors have provided critical insights into the molecular mechanisms of phyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 132 publications
0
3
0
Order By: Relevance
“…This W300 residue, of which the indole group has been called the "lock" [46], is crucial for binding the closed gate and latch loops of the receptor. Based on our modeling results and the above findings, we propose that this "lock" site stabilizes the ABI1-ACS7 complex, where the conserved tryptophan residue in ABI1 (W300) forms a water-mediated contact with ACS7, making it critical for interaction with the gate and latch loops [46,47,64,65]. These data demonstrate that the interaction interface between ABI1 and ACS7 overlaps with the PYL-PP2C interface, lending further support to a conserved mechanism of interaction between PP2Cs and their targets.…”
Section: Discussionmentioning
confidence: 67%
“…This W300 residue, of which the indole group has been called the "lock" [46], is crucial for binding the closed gate and latch loops of the receptor. Based on our modeling results and the above findings, we propose that this "lock" site stabilizes the ABI1-ACS7 complex, where the conserved tryptophan residue in ABI1 (W300) forms a water-mediated contact with ACS7, making it critical for interaction with the gate and latch loops [46,47,64,65]. These data demonstrate that the interaction interface between ABI1 and ACS7 overlaps with the PYL-PP2C interface, lending further support to a conserved mechanism of interaction between PP2Cs and their targets.…”
Section: Discussionmentioning
confidence: 67%
“…Thus, when treated with mandipropamid, PYR1 MANDI -expressing transgenic plants show increased drought resistance, without affecting the endogenous ABA. Because of the recent progress in deciphering the 3D structures of plant-hormone receptors (reviewed by Miyakawa and Tanokura [404]), this orthogonal ligand-receptor strategy can now be applied to other plant hormones. For example, a recent report found that a phthalimide derivative, AC94377, acts as an agonist of the GA receptor [61].…”
Section: Achievements and Prospects Of Chemical Geneticsmentioning
confidence: 99%
“…Plants perceive changes in their environment and, in turn, modulate the content and distribution of a small number of metabolites, referred to as plant hormones, which serve the integration and transmission of internal signals [ 13 , 14 , 15 ]. ‘Hormone’, from Greek hormān, meaning ‘to stimulate’ or ‘to set in motion’ in English, refers to small bioactive signaling molecules that can exert their action at a very low, submicromolar concentration [ 16 ].…”
Section: Introductionmentioning
confidence: 99%